2017
DOI: 10.1021/acs.joc.7b02731
|View full text |Cite
|
Sign up to set email alerts
|

Isocanthine Synthesis via Rh(III)-Catalyzed Intramolecular C–H Functionalization

Abstract: An efficient synthesis of substituted isocanthines has been achieved using an intramolecular Rh(III)-catalyzed C─H functionalization of alkyne-tethered indoles in the presence of catalytic tris(acetonitrile)pentamethyl-cyclopentadienylrhodium(III) hexafluoroantimonate and stoichiometric copper(II) acetate. This isocanthine synthesis tolerates a variety of electronically diverse 5-or 6-substituted indoles with N-tethered alkyne coupling partners and can also be extended to pyrrole derivatives for the synthesis … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 43 publications
(39 reference statements)
0
8
0
Order By: Relevance
“…In 2017, the group of Zhang and Fu reported a related approach to access substituted isocanthines, a class of tetracyclic γ‐carbolines possessing important clinical use to treat cardiovascular diseases and CNS disorders, among others (Scheme ) . The reaction relied on the formation of indole tert ‐butylimine intermediates in the presence of t BuNH 2 (Conditions B).…”
Section: Intramolecular Coupling With Alkynesmentioning
confidence: 99%
“…In 2017, the group of Zhang and Fu reported a related approach to access substituted isocanthines, a class of tetracyclic γ‐carbolines possessing important clinical use to treat cardiovascular diseases and CNS disorders, among others (Scheme ) . The reaction relied on the formation of indole tert ‐butylimine intermediates in the presence of t BuNH 2 (Conditions B).…”
Section: Intramolecular Coupling With Alkynesmentioning
confidence: 99%
“…demonstrated an effective amalgamation of substituted isocanthines utilizing an intramolecular Rh(III)‐ catalyzed C−H functionalization of alkyne‐tethered indoles within the sight of stoichiometric copper(II) acetate and catalytic tris(acetonitrile)pentamethylcyclopentadienyl rhodium‐(III) hexafluoroantimonate (Scheme 79). This isocanthine synthesis endures an assortment of electronically distinct 5‐ or 6‐substituted indoles with N‐tethered alkyne coupling associates and can likewise be reached out to pyrrole derivatives for the construction of annulated 5‐azaindoles [88] …”
Section: C−h Functionalization Of Pyrrolesmentioning
confidence: 99%
“…In 2018, Zhang and co-workers (Chen A. Y. et al, 2018) reported an efficient synthesis of isocanthines using a similar intramolecular strategy ( Figure 5B). The reaction proceeds in a one-pot two-stage fashion.…”
Section: Construction Of Polycyclic Heterocycles Fused Pyridines and mentioning
confidence: 99%